An evaluation of the point of sale services provided by Dutch-Bangla Bank Limited - Imtiaz, Md. Khalek (BARC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.